Co-fermentation of glycerol and sugars by Clostridium beijerinckii: Enhancing the biosynthesis of 1, 3-propanediol. (June 2021) - Fokum, Ernest; Zabed, Hossain M.; Ravikumar, Yuvaraj; Elshobary, Mostafa E.; Chandankere, Radhika; Zhang, Yufei; Yun, Junhua; Qi, Xianghui
Abstract: Sustainable biosynthesis of 1, 3-propanediol (1, 3-PD) from glycerol is limited by the need for an efficient strain, high cost of the fermentation medium, and substrate inhibition. To address these limitations, the optimal operational conditions for C . beijerinckii CCIC 22954 were determined using a single factor optimization approach. Batch fermentation was done using a cheap medium containing 7.5 g/L of corn steep liquor instead of yeast extract and glycerol, which led to 14.3 g/L of 1, 3-PD with a 0.48 g/g yield and 0.3 g/L.h productivity. To further increase the yield, the co-fermentation of glycerol and individual sugars (arabinose, glucose, sucrose, and xylose) was studied. A maximum 23.3 g/L of 1, 3-PD was obtained from the co-fermentation of glycerol (30 g/L) and glucose (10 g/L), with 0.78 g/g yield and 0.49 g/L.h productivity. These results showed the feasibility of co-fermentation technology in the sustainable biomanufacturing of 1, 3-PD by generally recognized as safe (GRAS), C. beijerinckii . Graphical abstract: Image 1